2021
DOI: 10.3390/genes12121971
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor 21 Promotes Chicken Adipocyte Differentiation at Least in Part via Activating MAPK/JNK Signaling

Abstract: The molecular mechanisms of transcription factor 21 (TCF21) in regulating chicken adipogenesis remain unclear. Thus, the current study was designed to investigate the signaling pathway mediating the effect of TCF21 on chicken adipogenesis. Immortalized chicken preadipocytes cell line (ICP), a preadipocyte cell line stably overexpressing TCF21 (LV-TCF21) and a control preadipocyte cell line (LV-control) were used in the current study. We found that the phosphorylation of c-Jun N-terminal kinases (JNK) was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The mechanism by which TCF21 affects malignant behaviors in GC is also noteworthy. TCF21 has been reported to influence multiple pathways, including the PI3K-AKT pathway and MAPK pathway [ 48 , 49 ]. However, further validation is needed to identify the direct target genes of TCF21 that regulate these downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which TCF21 affects malignant behaviors in GC is also noteworthy. TCF21 has been reported to influence multiple pathways, including the PI3K-AKT pathway and MAPK pathway [ 48 , 49 ]. However, further validation is needed to identify the direct target genes of TCF21 that regulate these downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microtubule affinity regulating kinase 4 can also promote lipid formation by inhibiting p38 and activating JNK1, and JNK activation promotes mesenchymal stem cell adipogenic differentiation [ 78 ]; these results seem to suggest that JNK plays opposite roles to ERK and p38 in adipogenesis. In this study, the differential expression of related genes also demonstrated that KRAS inhibition can activate the JNK pathway, thus promoting lipid formation by regulating PPARG and FABP4 [ 79 ]. After KRAS inhibition, the phosphorylation level of JNK increased, while the levels of ERK and p38 decreased at the same time, which suggests that KRAS plays important roles in lipid accumulation in MAC-T cells.…”
Section: Discussionmentioning
confidence: 99%